The Architectural and Planning Organization of the Closed Complexes for Winter Sports - SKOBLICKAYA, Yulia A.; SHEREMET, Anastasia A. (Journal of Environmental Management and Tourism, 2019)
This article is devoted to comprehensive study of architectural-planning and functional organization of indoor complexes for winter sports located in major cities. Design and construction of the described facilities will lead to even greater popularization of winter sports and will allow people to regularly visit skating rinks, ski trails, etc. The relevance of constructing such complexes in the largest cities of Russia is considered. A comprehensive analysis of the implemented, designed and under construction indoor complexes for winter sports in the world has been carried out. The article formulates the main recommendations regarding the location of the complexes in the structure of the major cities, the sizes of designated sites, taking into account the urban situation. Taking into account the analysis of design experience, regulatory documents, population surveys, this article provides basic recommendations on the architectural and planning solution for indoor complexes for winter sports, identifies functional elements that make up their composition. Variants of placement and blocking of the main functional zones were proposed, and the areas of the main groups of premises were set taking into account the placement of these complexes in urban structure.